Isolation of yeasts from raisins and Palm-juice and ethanol production in molasses medium - Rahman, Shafkat Shamim; Islam, Sarkar Mohammad Khairul; Rafiqul, Islam Mohammad; Khaled, Hossain; Kamrun, Nahar; Kumar, Roy Chapol; Uddin, Md Ekhlas; Choudhury, Naiyyum (© 2016 Indian Society for Education and Environment, 2016)
This article was published in the Indian Journal of Science and Technology [© 2016 Indian Society for Education and Environment ] and the definite version is available at : http://doi.org/10.17485/ijst/2016/v9i12/85509 The Journal's website is at: http://www.indjst.org/index.php/indjst/article/view/85509